Use of computerized anesthesia in children's anxiety and pain perception during dental care: protocol for a randomized clinical trial (Research, Society and Development, 2023)
This study was designed to evaluate the use of computerized anesthesia during dental care in children. The randomized controlled trial will be carried with 92 children aged 5-11 years. Children will be randomly assigned to receive conventional anesthesia - control group, or computerized anesthesia - intervention group. To measure the child's anxiety, the Dental Subscale of the Children’s Fear Survey Schedule - CFSS-DS and the VENHAM Picture Test Modified – VPTM will be used, as well as verification of heart rate. Coping style will be evaluated with The Monitor-Blunter Dental Scale - MBDS. The child's behavior will be assessed using the Brazilian version of the VENHAM Scale and pain will be assessed using the Faces Pain Scale – Revised (FPS-R) and the Face, Legs, Activity, Cry and Consolability (FLACC). Cortisol level will be evaluated before and after the procedure, through unstimulated saliva. Dentist’s stress will be evaluated using the visual analogue scale (VAS). Given the conflicting results regarding the benefits of computerized anesthesia in the literature, it is believed that the results will help define the best strategy to reduce perception of pain, anxiety and behavior during the pediatric dentistry consultation.